2013
DOI: 10.1007/s12298-013-0173-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water stress on antioxidant systems and oxidative parameters in fruits of tomato (Solanum lycopersicon L, cv. Micro-tom)

Abstract: The effects of different levels of water stress on oxidative parameters (H 2 O 2 and MDA), the total pool sizes of ascorbate, the activities of antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT), as well as the activities and relative transcript levels of the enzymes of ascorbate-glutathione cycle ascorbate peroxidase (APX), monodehydroascorbate reductase (MDHAR), dehydroascorbate reductase (DHAR) and glutathione reductase (GR) were studied in the fruit of tomato (Solanum lycopersicum L. cv. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 59 publications
5
49
0
1
Order By: Relevance
“…Ascorbate concentration in tomato fruit was also found to be reduced under high salinity (D'Amico et al, 2003), heat (Massot et al, 2013) and light stress conditions (Ioannidi et al, 2009;, all conditions favorable for BER appearance (Olle and Bender, 2009). Interestingly, fruit calcium concentration, the major known factor in BER initiation, has also been proposed to be positively correlated with ascorbate levels in tomato fruit (Premuzic et al, 1998) and the conditions favorable to BER, like salinity, drought and heat stress, were also found to increase ROS levels in tomato fruit (Leyva et al, 2013;Murshed et al, 2013Murshed et al, , 2014. Taking all these facts into account, there seems to be a connection between conditions that lower ascorbate concentrations and increase ROS levels to the susceptibility toward BER in tomatoes.…”
Section: Introductionmentioning
confidence: 99%
“…Ascorbate concentration in tomato fruit was also found to be reduced under high salinity (D'Amico et al, 2003), heat (Massot et al, 2013) and light stress conditions (Ioannidi et al, 2009;, all conditions favorable for BER appearance (Olle and Bender, 2009). Interestingly, fruit calcium concentration, the major known factor in BER initiation, has also been proposed to be positively correlated with ascorbate levels in tomato fruit (Premuzic et al, 1998) and the conditions favorable to BER, like salinity, drought and heat stress, were also found to increase ROS levels in tomato fruit (Leyva et al, 2013;Murshed et al, 2013Murshed et al, , 2014. Taking all these facts into account, there seems to be a connection between conditions that lower ascorbate concentrations and increase ROS levels to the susceptibility toward BER in tomatoes.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced water availability immediately affects cellular water status, solute transport, photosynthesis and transpiration (Murshed et al, 2013). Drought induces higher leakage of electrons toward O 2 during photosynthesis and respiration; this generates cellular oxidative stress, which enhances the production of reactive oxygen species (ROS) (Sánchez-Rodríguez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation level in the pulp was not influenced by the notirrigated conditions in fruits at harvest for the early harvest stages (H1 and H2), but a significant difference was observed at the last harvest stage or after ripening, R1-R3, where irrigated fruits had 50% less H 2 O 2 than non-irrigated fruits These changes indicated that limited water supply induced oxidative stress, like in tomato (Murshed et al, 2013). The high contents in H 2 O 2 in ripe fruits from non-irrigated trees can also be related in part to the significantly high respiration rates measured in these fruits since these ROS compounds are produced by an increase in mitochondrial activity (Tian et al, 2013).…”
Section: Effect Of a Reduction In Water Supply On Oxidative Stress Anmentioning
confidence: 86%
“…Other signals could also be implicated in ROS production such as ethylene, which is actively implicated in climacteric fruit ripening (Ebel et al, 1993). The increase in the content of reactive oxygen species in conditions of low water supply has been already shown by increasing the water stress intensity of tomato, another climacteric fruit (Murshed et al, 2013). However, MDA content did not present any difference between treatments, suggesting that if oxidation could induce membrane destruction, there is no direct correlation between MDA and H 2 O 2 contents in mango pulp.…”
Section: Effect Of a Reduction In Water Supply On Oxidative Stress Anmentioning
confidence: 99%